Pelatihan Kewirausahaan Dan Manajemen Pemasaran Di Sosial Media Pada UMKM Desa Nagurpane - Yulianita Lubis, Siska; Muhammad Safii; Andri Ekawati, Yuni (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
The utilization of social media in the digital era has become a primary key to the sustainability of Micro, Small, and Medium Enterprises (MSMEs), especially in rural areas with limited market access. Nagurpane Village possesses diverse economic potential, ranging from palm oil derivative products to handicrafts; however, its management remains traditional and confined to local marketing. This community service activity aims to enhance the human resource capacity of MSMEs in Nagurpane Village through entrepreneurship training and social media-based marketing management. The methods employed in this activity include field surveys, material preparation, intensive training execution, and direct practical assistance. The results of this program indicate a significant increase in participants' understanding of the importance of branding and digital marketing techniques. Participants are now capable of operating business accounts on social media platforms, conducting independent product photography, and understanding competitive pricing strategies. Despite challenges such as time constraints and digital infrastructure limitations in rural areas, the high enthusiasm of the participants served as the main supporting factor for the program's success. The conclusion of this activity emphasizes that digital transformation through online marketing education can expand the market reach of Nagurpane Village's MSMEs, increase sales volume, and strengthen local economic competitiveness amidst dynamic global market competition.